Linking Corporate Social Responsibility and Self-Determination Theory: Driving Employee Motivation, Engagement, and Organizational Performance in India - SAHILALI Saiyed (PT Advanced business journal, 2025)
This study investigates the impact of Corporate Social Responsibility (CSR) dimensions—economic, legal, environmental, ethical, and philanthropic—on employee motivation, engagement, and organizational performance within Indian non-profit organizations. Grounded in Corporate Social Responsibility Theory and Self-Determination Theory (SDT), the research explores how CSR initiatives fulfill employees’ psychological needs for autonomy, competence, and relatedness, thereby enhancing intrinsic and extrinsic motivation. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), the study confirms that intrinsic motivation significantly mediates the relationship between CSR and employee engagement, with extrinsic motivation having a weaker but still notable effect. Furthermore, employee engagement strongly influences organizational performance, reinforcing the role of internally driven motivation. The findings suggest that aligning CSR efforts with psychological needs can foster a motivated, engaged workforce, ultimately driving sustainable organizational outcomes. This research contributes both theoretically and practically by offering a strategic framework for leveraging CSR to enhance human resource effectiveness in the non-profit sector.